Biographical Sketch: George E. Bennett, MD (1885–1962) - Brand, Richard A. (Springer-Verlag, 2012)
This biographical sketch on George Bennett corresponds to the historic text, The Classic: Shoulder and Elbow Lesions Distinctive of Baseball Players (1947), available at DOI 10.1007/s11999-012-2335-2.